Reformulation of Dispute Resolution Mechanisms for Public Information Requests to Achieve Constructive Law Enforcement and Legal Certainty - Peter Jeremiah Setiawan; Xavier Nugraha; Elma Putri Tanbun (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2021)
The nature of law enforcement in resolving multi-dimensional information disputes has a logical consequence on the need for constructive law enforcement. This research aims to examine the forms of law enforcement that exist in resolving disputes over requests for public information and to formulate a constructive mechanism to realize a series of law enforcement procedures with legal certainty. This research is normative legal research using a statutory and conceptual approach. The results showed that law enforcement in the settlement of public information disputes consists of the objection, non-litigation adjudication, and litigation covering civil, state administration, and criminal law. In this case, The Criminal law instruments are placed as the final law enforcement if the relevant public agency does not carry out a decision that has permanent legal force. In addition, in the context of realizing comprehensive and constructive law enforcement, a Memorandum of Understanding was held between the Information Commission and the Police to synergize and effectively implement the criminal law as a final resort.